Handel's Messiah spectacular (Cultural Center of the Philippines, Cultural Promotions Division, 1988)
"A special performance of the Easter portion of Handel's Messiah, featuring the Philippine Philharmonic Orchestra, Francisco F. Feliciano, conductor."